2014
DOI: 10.1590/s1806-66902014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Water use efficiency of marandu palisadegrass as affected by nitrogen and sulphur rates

Abstract: -This study aimed to evaluate the effects of combination of nitrogen and sulphur fertilizations on water consumption and water use efficiency by marandu palisadegrass (Brachiaria brizantha cv. Marandu). The experiment was carried out in a greenhouse, using a Typic Quartzipsamment. Five nitrogen rates (0; 100; 200; 300 and 400 mg dm -3 ) were combined with five sulphur rates (0; 10; 20; 30 and 40 mg dm -3 ) in a fractionated 5 2 factorial, with four replications. The leaf area was harvested three times at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…[22]. A similar result was obtained by Artur et al [39] where the increase of N has reduced the WUE in Marandu grass that showed a hig application of nitrogen can reduce stress in aquatica. the WUE in Marandu grass that showed a high application of nitrogen can reduce stress in I.…”
supporting
confidence: 83%
“…[22]. A similar result was obtained by Artur et al [39] where the increase of N has reduced the WUE in Marandu grass that showed a hig application of nitrogen can reduce stress in aquatica. the WUE in Marandu grass that showed a high application of nitrogen can reduce stress in I.…”
supporting
confidence: 83%
“…Mombaça possibly lead to a larger photosynthetic area, resulting in higher forage mass, as supported by the higher SPAD, although the difference in LAI was not statistically significant. The low rainfall in the present study particularly in the middle of the experimental period can be influenced by soil water availability and atmospheric evaporative demand (Artur et al, 2014). Moreover, each species adapted differently, which explains the present results.…”
Section: Resultsmentioning
confidence: 48%
“…The ryegrass plants tended to accumulate more nitrogen during the wet season, an expected result if we consider that water plays an important role in the nitrogen uptake by plants, and thus in the absorption of other nutrients (Artur et al, 2014). These authors found significant interaction between nitrogen and sulfur rates in terms of the amount of water consumed by Brachiaria brizantha plants.…”
Section: Spatial and Seasonal Nutritional Enrichments In The Study Rementioning
confidence: 62%